Application of multivariate morphometry to access the morphological variability in sauropod teeth (Zubía, 2024)
This study aims to explore and characterize the morphological variabilityin sauropod teeth through multivariate statistics using Principal ComponentAnalysis (PCA), Discriminant Function Analysis (DFA) and Clusteranalysis, and access the potential of these methods to classify them. Weanalyzed a sample of spoon-shaped, spatula-shaped, and compressed conechisel-shaped teeth. The apicobasal apex length, the total length of the distalapex margin, and the total length of the mesial apex margin are identifiedby PCAs as the most important variables affecting morphological variability.The DFAs enabled to differentiate the morphospaces occupation of themain sauropod groups analyzed (e.g., Camarasauridae, Turiasauria). Clusteranalysis allowed differentiate teeth with low from moderate to high SI. Themorphospaces of spoon-shaped, spatula-shaped, and compressed conechisel-shaped teeth were differentiated, some showing a slight overlap. Thetooth wear seems to influence the obtained results, and teeth with moderateor strong wear should be excluded in future analyses.